Counseling on Vaname Shrimp Cultivation Using the Biofloc Method to Communities in Dowora Village, Tidore Kepulauan City - Sardi Titaheluw, Syahnul; Tangke, Umar; Talib, Ahmaad; Laitupa, Ibnu; Bafagih, Aisyah; Andriani, Rovina; Tan, Fathnun; Lating, Ali (Universitas Muhammadiyah Palembang, 2022)
The purpose of carrying out this community service is to provide information and understanding to the community in the Dowora Village, East Tidore District about vannamei shrimp farming using the biofloc method. The community service was carried out in August 2022, at the Office of the Office of Food Security, City of Tidore Islands. The counseling method is carried out in the form of lectures, discussions and questions and answers. Materials from this counseling include management of vannamei shrimp cultivation; feed management; water use and water quality parameters; vannamei shrimp farming with the biofloc system, and introduction to the types of ponds that can be used for vannamei shrimp farming activities with the biofloc system. During the extension activities, the community of prospective vannamei shrimp cultivators was very active in asking questions and discussing the material provided. The conclusion that can be drawn from this PKM activity is that the community is able to understand the material presented about vannamei shrimp farming using the biofloc method, the material presented is acceptable and then pond repairs will be carried out in preparation for cultivation.